FAKTOR-FAKTOR POSITIF UNTUK MENINGKATKAN POTENSI KADER POSYANDU DALAM UPAYA MENCAPAI KELUARGA SADAR GIZI (KADARZI) - Trintrin T. Mudjianto; Tjetjep S. Hidayat; Hermina Hermina; Ema Luciasari; Nurfi Afriansyah; Noviati Fuada (Persagi, 2003)
POSITIVE FACTORS TO INCREASE THE POTENTIAL OF CADRE'S INTEGRATED SERVICES POST IN ORDER TO ACHIEVE THE NUTRITION AWARENESS FAMILY.Background: One of indicators of the nutrition awareness family (KADARZI) is family member's attendance for health and growth monitoring to POSYANDU, especially children aged 1-5 years (8ALITA) and pregnant women. The successful of BALITA growth monitoring depends on the cadre ability to conduct the POSYANDU activities, among others.Objectives: The objective of this study is to describe the positive factors related to POSYANDU cadre ability to increase the family nutrition awareness regarding BALITA growth monitoring.Methods: Cross sectional survey was used in this study. The study was conducted in 16 POSYANDU of the Kampar and Pelalawan Districts, Riau Province, and covered 58 cadres as respondents. Interview with respondents was used to collect data using a questionnaire.Results: All cadres are women and most of them are 21-40 of age about 50 percent that having high school education, and almost all of respondents work as housekeeper. Motivation to be cadres is mainly for helping the community member or village development. About 53 percent of cadres had never received training, and the rest of cadres had received training only once although they have been a cadre for more than two years. Besides, most of the POSYANDU has no materials or booklets for community education. About 71 percent cadres have no booklet and about 52 percent have never given information to the community because they have no knowledge in nutrition counseling. Cadre knowledge in growth curve interpretation in the growth chart is very low; it was only nine percent of cadre that able to interpret growth curve correctly. Only two percent cadre knows that the weight change in monthly weighing should be told to mother in nutrition counseling. In order to increase nutrition awareness family, particularly in growth monitoring, the POSYANDU should be revitailzed by improving the cadre ability in growth graph interpretation as well as growth monitoring, nutrition counseling, and provide means of communication in POSYANDU activities.Keywords: POSYANDU cadre, nutrition awareness family, POSYANDU revitalization